Generative AI-Induced Emotions in EFL Classrooms: Effects and Students’ Regulation Strategies - Wangdi, Thinley; Rofiah, Nur Lailatur (Journal of Education Culture and Society, 2026)
Aim. This interpretive qualitative study explored Thai EFL students’ emotional experiences in a seven-week generative (Gen) AI-integrated classroom, the perceived impacts of these emotions, and the emotion regulation strategies (ERSs) employed by students in response to their emotional experiences. Methods. The data collected using written interviews on Google Docs from 22 purposively selected second-year university students after the intervention were thematically analysed. Results. The study found that students experienced both negative emotions (e.g., frustration, discouragement, dissatisfaction, anxiety, boredom, and confusion) and positive emotions (e.g., excitement, confidence, and curiosity) in a Gen AI-integrated classroom. Positive emotions that students experienced in a Gen AI-integrated classroom enhanced their learning enjoyment, content understanding, confidence, motivation, and engagement, whereas negative emotions reduced their motivation and classroom focus and led to poorer language development. To regulate their emotions, students employed both antecedent-focused and response-focused strategies ERSs. Conclusions. The study concludes that Gen AI tools induce emotions in learners and that these emotions influence their learning experiences in several ways. It also concludes that learners regulate their emotional experiences in Gen AI-integrated classrooms. Practical implications for ELT policymakers, educators, and students, along with recommendations for future research, are also provided.